Sustainability Reporting Ecosystem and IFRS S1 and S2: How Accounting Research can assist its Implementation - Pratama, Arie; Dewi, Nanny; Sofia, Poppy; Muhammad, Kamaruzzaman; Megawati, Lokita Rizky (Journal of Ecohumanism, 2024)
This paper describes how the accounting research agenda is affected by the issuance and implementation of the International Financial Reporting Sustainability Disclosure Standards (IFRS S1 and IFRS S2). The new IFRS S1 and S2 were launched on June 26, 2023, and are effective from January 1, 2024. The implementation of IFRS S1 and S2 will be particularly interesting as this is the first time that financial and sustainability reporting will be integrated into a company’s corporate reporting. Given the relatively short timeframe since its introduction, there may be limitations in assessing the full impact or implications of these standards. Hence, this study analyzes various research opportunities related to the implementation of IFRS S1 and S2. Due to the limited literature that discusses the implementation of IFRS S1 and S2, this study applies the review method, i.e., it conducts a review based on existing research on IFRS S1 and S2, as well as research examining existing sustainability accounting and reporting aspects. This study analyzes research opportunities in the areas of (1) financial accounting, (2) management accounting, (3) auditing, and (4) accounting information systems. This study contributes to the research area of the sustainability reporting ecosystem to facilitate the smooth implementation of IFRS S1 and S2 in practice.